Establishment of grass belts in interlinear area of orchards with different grass mixtures and perennial ryegrass with application of hydrogel - Lakić Željko; Malić Nenad; Misimović Milutin (Agroznanje, 2013)
The research was performed in 2011 and 2012 in two locations: the experimental field of Agricultural Institute of RS and Stranjani, a village near Banja Luka. In location Stranjani the experiment was set up in a young orchard of pear, while in the location Delibašino Selo it was set up in an experimental mixed plantation of fruit trees (plum, apricot, peach). Four grass mixtures and perennial ryegrass were used for this purpose. The experiments were set in four repetitions on a brown valley soil and vertisol. We applied a classic soil processing in Delibašino Selo and reduced soil processing in Stranjani. Before sowing on both locations hydrogel was introduced into soil in both locations. Floristic content, green and dry mass yield, number of mulching, analysed content of plant mass of first swath, covering - density of crops and soil moisture content were observed during this two-year long research. Green biomass and dry mater yield in a first swath of 2011 in Delibasino Selo were higher in all researched variants on surfaces where hydrogel was used. In a location where reduced soil processing was applied, a share of other plant species in green biomass of first swath was higher during both years of the research. The highest covering - density of crops in Delibasino Selo location had a mixture TS/1, while on Stranjani location it was mixture TS/4.